1996
DOI: 10.1152/jn.1996.75.4.1309
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of the B31/B32 pattern initiators innervating the I2 muscle of the buccal mass during normal feeding movements in Aplysia californica

Abstract: 1. B31 and B32 are pattern-initiator neurons in the buccal ganglia of Aplysia. Along with the B61/B62 neurons, B31/B32 are also motor neurons that innervate the 12 buccal muscle via the I2 nerve. This research was aimed at determining the physiological functions of the B31/B32 and B61/B62 neurons, and of the I2 muscle. 2. Stimulating the I2 muscle in the radula rest position produces radula protraction. In addition, in behaving animals lesioning either the muscle or the I2 nerve greatly reduces radula protract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 0 publications
2
115
0
Order By: Relevance
“…Previous studies in this system have demonstrated that the durations of spike trains from identified motor neurons Chiel 1993a, 1993b), and durations of EMG from the I2 muscle (reflecting the activity of the B31/B32 and B61/B62 motor neurons; Hurwitz et al 1996), can be related to behavior. The times that were measured are indicated in Fig.…”
Section: Recording Analysismentioning
confidence: 95%
See 3 more Smart Citations
“…Previous studies in this system have demonstrated that the durations of spike trains from identified motor neurons Chiel 1993a, 1993b), and durations of EMG from the I2 muscle (reflecting the activity of the B31/B32 and B61/B62 motor neurons; Hurwitz et al 1996), can be related to behavior. The times that were measured are indicated in Fig.…”
Section: Recording Analysismentioning
confidence: 95%
“…Previous studies have demonstrated that all critical motor neuronal elements for controlling the feeding apparatus (the buccal mass) can be monitored by recording directly from 1) the protractor muscle (I2), whose activation is an obligatory first step for effective feeding movements and whose EMG patterns represent the activity of interneurons/motor neurons B31/B32 and motor neurons B61/B62 (Hurwitz et al 1996); 2) the radular nerve (RN), which contains axons of the motor neurons B8a/B8b controlling closure of the grasper Chiel 1993a, 1993b); 3) buccal nerve 2 (BN2), which contains axons of the motor neurons controlling the jaw musculature, B10, B6, B9, B3, B38, and B43 (Church and Lloyd 1994;Lu et al 2013;Morton and Chiel 1993b); and 4) buccal nerve 3 (BN3), which contains axons of motor neurons controlling some of the intrinsic muscles of the grasper (e.g., B15/B16; Church and Lloyd 1994;Cohen et al 1978) and a multiaction neuron, B4/B5 (Church and Lloyd 1994;Warman and Chiel 1995;Ye et al 2006b). Nerves RN, BN2, and BN3 are referred to as n1, n5, and n4 in Scott et al (1991).…”
Section: Recording In Vivo Feeding Motor Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single twophase cycles of motor programs consisting of protraction and retraction phases were induced every 2 min by stimulating CBI-2 at 8 -10 Hz with 10 msec current pulses. Electrical activity in nerve I2 was used to monitor protraction because this nerve contains axons of protraction phase motor neurons B31/32 and B61/62 (Hurwitz et al, 1996). Sustained depolarization in B4/5 was used to monitor retraction (Church and Lloyd, 1994;Jing and Weiss, 2001).…”
Section: Physiological Action Of Fcapsmentioning
confidence: 99%